Analisis Prinsip Dasar Evaluasi Pembelajaran di SDN Duri Kosambi 09 Pagi - Ina Magdalena; Dini Damayanti; Muhammad Sodiq Mardiyanto; Siti Annisa Erika; Zairah Zahra (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This study aims to analyze the basic principles of learning evaluation that are applied at SDN Duri Kosambi 09 Pagi. Evaluation of learning is an important part of the educational process to ensure the effectiveness and quality of learning provided to students. In this study, the authors used qualitative research methods involving direct observation, interviews, and document analysis as data collection techniques. The results of this study are expected to provide insight into the basic principles of learning evaluation applied at SDN Duri Kosambi 09 Pagi.